2021
DOI: 10.14488/bjopm.2021.014
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation of Criteria Weights for Multicriteria Models: Bibliometrics, Typologies, Characteristics and Applications

Abstract: Goal: This study aims to review and classify the main methods of criteria weights definition.Design / Methodology / Approach: From a systematized search were articles selected and analyzed, covering a timeline between 1949 and 2020.Results: Fifty sex methods were identified and discussed. Most (49) are subjective, eleven are objectives and three are hybrids. Considering the aggregation procedure, 33 are compensatory and 23 are non-compensatory. Most of the methods are for a single decision maker and just eleve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 73 publications
(152 reference statements)
0
4
0
Order By: Relevance
“…In the later analyses, we implemented equal weights. However, it should be noted that in the literature, various proposals exist for establishing weights [59][60][61][62][63][64]. Tzeng et al [65] classifies weighting methods as objective when weights are computed from outcomes and subjective when they depend only on the preferences of decision-makers.…”
Section: The Hellwig's Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the later analyses, we implemented equal weights. However, it should be noted that in the literature, various proposals exist for establishing weights [59][60][61][62][63][64]. Tzeng et al [65] classifies weighting methods as objective when weights are computed from outcomes and subjective when they depend only on the preferences of decision-makers.…”
Section: The Hellwig's Methodsmentioning
confidence: 99%
“…The third class is the combination of subjective and objective weighting methods. Da Silva et al [62] identified and discussed more than 50 methods, of which 49 are subjective, 7 are objective, and others are hybrid.…”
Section: The Hellwig's Methodsmentioning
confidence: 99%
“…Multi-criteria decision-making (MCDM) is an important field in operations research and decision analysis, providing structured approaches to handle complex decision problems involving multiple, often conflicting, criteria [ 1 , 2 , 3 ]. The motivation for this study is related to the assessment of criteria weights and whether they are independent or dependent on one another [ 4 , 5 , 6 , 7 , 8 ] within the multi-criteria procedure. This issue plays a critical role in shaping the decision process and the outcome [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary for leaders to be able to determine the relative importance of the factors or criteria that influence the success of projects. Despite existing efforts to There are several published works that discuss establishing criteria weights in the context of project evaluation including da Silva et al (2021), Roy, Das, Kar and Pamučar (2019), Šenitková, Burdová and Vilčeková (2010), Yi, Li and Zhang (2019) and Zagonari (2016). However, despite the great advances achieved in these studies, most of them do not use modeling based on trade-offs for the treatment of the data collected regarding the importance of criteria.…”
Section: Introductionmentioning
confidence: 99%